Analysis of Cosmic Rays' Atmospheric Effects and Their Relationships to Cutoff Rigidity and Zenith Angle Using Global Muon Detector Network Data. Issue 12 (14th December 2019) - Mendonça, R. R. S.; Wang, C.; Braga, C. R.; Echer, E.; Dal Lago, A.; Costa, J. E. R.; Munakata, K.; Li, H.; Liu, Z.; Raulin, J.‐P.; Kuwabara, T.; Kozai, M.; et al.
Abstract: Cosmic rays are charged particles whose flux observed at Earth shows temporal variations related to space weather phenomena and may be an important tool to study them. The cosmic ray intensity recorded with ground‐based detectors also shows temporal variations arising from atmospheric variations. In the case of muon detectors, the main atmospheric effects are related to pressure and temperature changes. In this work, we analyze both effects using data recorded by the Global Muon Detector Network, consisting of four multidirectional muon detectors at different locations, in the period between 2007 and 2016. For each Global Muon Detector Network directional channel, we obtain coefficients that describe the pressure and temperature effects. We then analyze how these coefficients can be related to the geomagnetic cutoff rigidity and zenith angle associated with cosmic ray particles observed by each channel. In the pressure effect analysis, we found that the observed barometric coefficients show a very clear logarithmic correlation with the cutoff rigidity divided by the zenith angle cosine. On the other hand, the temperature coefficients show a good logarithmic correlation with the product of the cutoff and zenith angle cosine after adding a term proportional to the sine of geographical latitude of the observation site. This additional term implies that the temperature effect measured in the Northern Hemisphere detectors is stronger than that observed in the Southern Hemisphere. The physical origin of this term and of the good correlations found in this analysis should be studied in detail in future works. Key Points: Pressure and temperature effects observed by ground muon detectors was experimentally analyzed inrelation to cutoff rigidity and zenith angle The best correlation was found when considering product between cutoff rigidity and zenith angle secant (pressure) or cosine (temperature) The temperature effect only shows a global trend if a relationship with the sine of each detector's geographic latitude is included